2017
DOI: 10.1016/j.ajme.2016.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A detailedin vitrostudy of naproxen metal complexes in quest of new therapeutic possibilities

Abstract: The present study was designed to investigate the in vitro anti-inflammatory, antimicrobial, cytotoxic and antioxidant effects of Naproxen metal complexes. Methodology: The anti-inflammatory activity was evaluated by HRBC membrane stabilization method while antimicrobial activity by disk diffusion method. The cytotoxicity was evaluated by brine shrimp lethality bioassay and compared with vincristine sulfate. Antioxidant potential was evaluated in terms of DPPH radical scavenging potential, ABTS scavenging pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In complex 1 , the NO 3 − anion strongly binds to the metal center, in contrast to the counter ions BF 4 − , ClO 4 − and SbF 6 − counter ions. It has also been shown that silver(I) complexes with other drugs, e.g., naproxen, have strong antimicrobial properties and may be good candidates as antibacterial agents [ 60 ]. The studied silver(I) complexes of miconazole are much less active against Gram-negative bacteria than against Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…In complex 1 , the NO 3 − anion strongly binds to the metal center, in contrast to the counter ions BF 4 − , ClO 4 − and SbF 6 − counter ions. It has also been shown that silver(I) complexes with other drugs, e.g., naproxen, have strong antimicrobial properties and may be good candidates as antibacterial agents [ 60 ]. The studied silver(I) complexes of miconazole are much less active against Gram-negative bacteria than against Gram-positive bacteria.…”
Section: Resultsmentioning
confidence: 99%
“…Naproxen (Hnap), a prominent member of NSAIDs, has been mainly used in the treatment of headaches and fevers based on its analgesic and antipyretic features [25][26][27][28]. There are several papers in which silver-naproxen complexes are synthesized and their biological properties evaluated, showing better biological activities than naproxen [29][30][31][32]. The synthesis of novel silver(I)-naproxen complexes means designing of a new chemotherapeutic agent, and therefore, significant efforts should be made to synthesize the complexes and investigate their cytotoxic activity against both different types of cancer cell lines and normal cells.…”
Section: Introductionmentioning
confidence: 99%